Prenatal diagnosis of fetal congenital cystic adenomatoid malformation of the lung using three-dimensional ultrasound: Comparison between the 20th and 21st centuries - Hsing-Fen Tsai; Yueh-Chin Cheng; Huei-Chen Ko; Lin Kang; Pei-Yin Tsai; Chen-Hsiang Yu; Chiung-Hsin Chang; Fong-Ming Chang (Taiwanese Journal of Obstetrics & Gynecology, 2013)
Objective: Congenital cystic adenomatoid malformation of the lung (CCAML) is one of the most common lung lesions diagnosed prenatally. In order to compare the trends and improvements of prenatal diagnosis of CCAML, we herein retrospectively reviewed our cases of fetal CCAML detected by three-dimensional ultrasound (3-D US) between two centuries. Materials and Methods: We reviewed our computer database of prenatal diagnosis of CCAML in National Cheng Kung University Hospital from October 1994 to November 2011. All of the fetuses were initially scanned by two-dimensional (2-D) US to locate the region-of-interest (ROI). Then, the 3-D probe was used to scan all of the ROI systematically and mechanically, and the images were stored in the laser discs for further 3-D visualization and reconstruction. To compare the characteristics at prenatal diagnosis of CCAML between the 20th and 21st centuries in our hospital, Chi-square tests were undertaken. A p value <0.05 was considered as statistically significant. Results: In total, 58 fetuses with CCAML were depicted by 3-D US in utero (12 cases were diagnosed in the 20th century and 46 cases in the 21st century). The ranges of gestational age at prenatal diagnosis of CCAML by 3-D US in the 20th century were between 15 and 36 weeks (mean=24 weeks), and were between 16 and 31 weeks (mean=22 weeks) in the 21st century. Moreover, nine cases (75%) were diagnosed at the second trimester in the 20th century, whereas 44 cases (96%) were diagnosed at the second trimester in the 21st century. Conclusion: The advancement of 3-D US has remarkable advantages in adding novel visual depiction of a 3-D lesion of a 3-D fetus in 3-D US after reconstruction, and thus assists substantially in the prenatal diagnosis and genetic consultation of CCAML. Furthermore, the trend analysis in this series showed a significantly earlier gestational age at prenatal diagnosis of CCAML in the 21st century than that in the 20th century.